2016
DOI: 10.4209/aaqr.2015.01.0018
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Based Estimates of Aerosol Washout and Recovery over India during Monsoon

Abstract: Large aerosol optical depth (AOD) observed over the Indian subcontinent during the monsoon season in the satellite data challenges the common notion of aerosol washout by monsoon rain. Here, we examined recovery of aerosol field after washout by monsoon rain over various rainfall homogeneous zones of India in view of the duration of rainfall, recovery time and source strength. Mean (± 1 standard deviation) seasonal aerosol optical depth, AOD is highest over the central northeast 1 (0.74 ± 0.22) followed by cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…AOD trends during the winter season are increasing over eleven out of twelve selected regions with six being statistically significant ( Table 2). Thus the reduced rainfall over most of the selected regions reduces the suppression of atmospheric aerosols through rainfall washout processes, which is consistent with investigations by a number of authors (e.g., [110,115,[121][122][123]). Therefore, the trends in precipitation, showing an inverse pattern to the trends in AOD could be responsible for the observed aerosol load.…”
Section: Association Between Trends In Aod and Meteorological Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…AOD trends during the winter season are increasing over eleven out of twelve selected regions with six being statistically significant ( Table 2). Thus the reduced rainfall over most of the selected regions reduces the suppression of atmospheric aerosols through rainfall washout processes, which is consistent with investigations by a number of authors (e.g., [110,115,[121][122][123]). Therefore, the trends in precipitation, showing an inverse pattern to the trends in AOD could be responsible for the observed aerosol load.…”
Section: Association Between Trends In Aod and Meteorological Parameterssupporting
confidence: 91%
“…Zhu et al [121] have reported an increase in aerosol concentration over China due to weakening of the East Asian Summer Monsoon. Chowdhury et al [122] reported that rainfall suppresses the dust emission and the soil moisture prevents the post-precipitation aerosol build up. Similarly, analyzing aerosol trends over East Africa, Makokha et al [123] and Boiyo et al [115] attributed the negative trends in AOD to the wet deposition process.…”
Section: Association Between Trends In Aod and Meteorological Parametersmentioning
confidence: 99%
“…The largest reduction is observed over the eastern IGP and along the west coast of India. In this season, PM2.5 level remains lower than 40 g/m 3 over entire India except for the arid region in the west (where the monsoon rain is scanty) and the western IGP including Delhi NCR (where the emission strength is so high that the aerosol recovery overcompensates the loss due to washout [32]). However, we note that PM2.5 does not meet the 24-hr WHO-AQG (25 g/m 3 ) on most of the days in most parts a b Figure 5.…”
Section: Spatial Pattern In Pm 25 Concentration Over Indiamentioning
confidence: 90%
“…Large exposure in many districts, especially in the IGB surrounding the Delhi national capital region suggests that anthropogenic source strength is large enough to replenish the atmosphere with pollutants rapidly during the dry days. 45 This is worrisome as even the monsoon rain is not enough to cleanse the atmosphere of pollutants to curb the exposure at least below the Indian air quality standard in this part of the country. The annual PM 10 exposure statistics in India is summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…PM 10 exposure in this season remains in the range 41–100 μg m –3 over most parts of India except over Delhi national capital region where it exceeds 100 μg m –3 . Large exposure in many districts, especially in the IGB surrounding the Delhi national capital region suggests that anthropogenic source strength is large enough to replenish the atmosphere with pollutants rapidly during the dry days . This is worrisome as even the monsoon rain is not enough to cleanse the atmosphere of pollutants to curb the exposure at least below the Indian air quality standard in this part of the country.…”
Section: Resultsmentioning
confidence: 99%